STRATEGI KOMUNIKASI KOMISI PENYIARAN INDONESIA DAERAH (KPID) RIAU DALAM MENGOPTIMALKAN PROGRAM LITERASI MEDIA TERHADAP PEMIRSA TELEVISI DI RIAU - Sari, Yesi Ratna; Lubis, Evawani Elysa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The television show is not only have a positive impact, but also the negative impact if not filtered properly, the impact would affect the behavior of television viewers. The majority of television shows are currently only prioritize entertainment, and the exclusion of education inside them. KPID has been have some strategys to bring the desired goals. This research aims to determine how the communication strategy communication of Komisi Penyiaran Indonesia Daerah (KPID) Riau in optimizing media literacy programs to television viewers in Riau and the obstacles encountered in performing that strategy communication of KPID in optimizing media literacy programs to television viewers in Riau.This research was conducted in (KPID) Riau Jl. Gajah Mada No. 200 Pekanbaru. for the record, this research using deskriptif kualitatif metode and analisis model data interactive miles and Huberman. Informants in this research are the commissioner of KPID Riau, students, and perents. Data collection techniques are using observations, interviews and documentations.The results of the reasearch showed that strategy communication of Komisi Penyiaran Indonesia Daerah (KPID) Riau so obvious a way to optimize the literacy of media between knowing a target communications, communications media selection, message communication assessment purposes, the role of communicators in the communication to the charms and the credibility of the source, the formation of KCM and KCSI, and cooperation. As for the KPID constraints in optimizing media literacy program is the community, the lack of public understanding of media literacy, as well as the public areas that are difficultKey Word :Strategy of communication, Audience, media literacy.